2015
DOI: 10.3390/toxics3010063
|View full text |Cite
|
Sign up to set email alerts
|

Mercury, Lead, Cadmium, Arsenic, Chromium and Selenium in Feathers of Shorebirds during Migrating through Delaware Bay, New Jersey: Comparing the 1990s and 2011/2012

Abstract: Understanding temporal changes in contaminant levels in coastal environments requires comparing levels of contaminants from the same species from different time periods, particularly if species are declining. Several species of shorebirds migrating through Delaware Bay have declined from the 1980s to the present. To evaluate some contaminants as cause for the declines, we examine levels of mercury, lead, cadmium, arsenic, chromium and selenium in feathers of red knot (Calidris canutus, N = 46 individuals), sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
4
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 49 publications
3
28
4
2
Order By: Relevance
“…In a similar manner, this work is also at variance with the work of [17] who reported a lower chromium concentration of 0.23±0.03mg/kg and 0.18±0.02mg/kg in the liver of House Sparrows from urban and rural habitats in southern Finland. This recent work is not in agreement with the research work of [18] who reported a higher chromium concentration levels in the shorebirds such as Red knot, Sanderling and Semipalmated sandpiper with a chromium concentration of 578±83 mg/kg, 764±260mg/kg and 1149±294mg/kg respectively in Delaware Bay in New Jersey, USA and the reasons could be differences in species, location and methods of contaminant analysis. From this research finding, the concentration of chromium in all the organs of the said species was below threshold of 50 mg/kg as recommended by WHO [19].…”
Section: Discussioncontrasting
confidence: 94%
“…In a similar manner, this work is also at variance with the work of [17] who reported a lower chromium concentration of 0.23±0.03mg/kg and 0.18±0.02mg/kg in the liver of House Sparrows from urban and rural habitats in southern Finland. This recent work is not in agreement with the research work of [18] who reported a higher chromium concentration levels in the shorebirds such as Red knot, Sanderling and Semipalmated sandpiper with a chromium concentration of 578±83 mg/kg, 764±260mg/kg and 1149±294mg/kg respectively in Delaware Bay in New Jersey, USA and the reasons could be differences in species, location and methods of contaminant analysis. From this research finding, the concentration of chromium in all the organs of the said species was below threshold of 50 mg/kg as recommended by WHO [19].…”
Section: Discussioncontrasting
confidence: 94%
“…This may be due to the differences in the feeding behaviour and diet feed on by both birds. Our research work is also at variance with the work of [20] who reported a higher cadmium concentration of 19±4mg/kg, 14±3mg/kg and 48±9mg/kg in feathers of shorebirds (Red knot, Sanderling and Semipalmated sandpiper respectively) migrating through Delaware Bay New Jersey in USA. Equally, cadmium concentration in eggs of Black headed orioles in this present research work is at variance with the research work of [21] who also reported a higher cadmium concentration of 0.82±0.25mg/kg and 5.21±0.17mg/kg in yolk and shell of Black headed gull in Poland.…”
Section: Discussioncontrasting
confidence: 52%
“…Birds are predominantly susceptible to the effects of anthropogenic activities in the environment and they have been recognized as good indictors of environmental contamination because of their abundance, wide distribution, feeding at different tropic levels, and their long life span [10][11][12]. With global change and increasing levels of industrial, commercial and agricultural contaminants it is important to study particular species living in a sensitive habitat [13] such as agricultural ecosystem for example Daudu, Buruku and Adega in Benue State, Nigeria because cadmium is capable of causing kidney damage [14] in population of wild birds. Cadmium may also enter the environment mainly through the ground, because it is found in manures and pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…En las cáscaras de huevos, las rutas fisiológicas que sigue el Hg en el ave durante el periodo reproductivo y en la dieta posiblemente tengan mucho que ver con su acumulación, así como el hábitat en el que se encuentre y el grado de exposición donde realizan sus actividades (Norheim, 1987;Boening, 2000;Burger, 2002;Carbonell et al, 2007;Burger et al, 2015).…”
Section: Procedimiento De Laboratoriounclassified
“…El litoral sur del golfo de Cariaco conforma parte geopolítica de cuatro de los quince municipios del estado Sucre, siendo un área de gran interés ecológico, pesquero y turístico; está altamente urbanizado y alberga una colonia permanente de anidación del Alcatraz, vecina a la población de San Antonio del Golfo (Municipio Mejía). En tal Desde hace varias décadas, las aves marinas vienen siendo utilizadas como biomonitores usuales de polución en ecosistemas marino-costeros, pues son especies longevas y generalmente están en el tope de las cadenas alimenticias razón por la cual pueden magnificar contaminantes toxigénicos (Furness & Camphuysen, 1997;ICES, 1999;Burger & Gochfeld, 2000;Burger, 2002;Boyd et al, 2006;Durant et al, 2009;Carravieri et al, 2013;McCormick et al, 2014;Burger et al, 2015;O'Hanlon, 2016). Adicionalmente, los tóxicos acumulados en sus plumas y sus huevos pueden cuantificarse sin detrimento del ave; de igual modo, la ecología y fisiología de la mayoría de las aves marinas ha sido relativamente bien estudiada lo cual facilita la interpretación de los datos en tejidos contaminados (ICES, 1999).…”
unclassified